PENGARUH KOMPENSASI FINANSIAL TERHADAP LOYALITAS KARYAWAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI - Karim, Jichan Zairah M. Nur; Jabid, Abdullah W; Kamis, Ruslan A (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2023)
ABSTRACTObjective: This study aims to determine the effect of financial compensation on loyalty through organizational commitment. This research is a type of quantitative research, because the research method is based on positivistic (concrete data), the research data is in the form of numbers that will be measured using statistics as a means of calculating the test to produce a certain conclusion. The population in this study were all employees of PT. Rum Timur Raya has 100 employees who are still actively working.Methodology: The data analysis method used is multiple linear regression using the SPSS 20.0 program. and the Partial Least Square (PLS) approach using the SmartPLS 3.8 statistical program.Finding: The first, second, third, and fourth (H) hypotheses were accepted because the t statistic value was greater than t table, and the p value was smaller than alpha 0.05.Conclusion: The results of this study indicate that: (1) Financial Compensation has a positive and significant effect on Employee Loyalty; (2) Financial Compensation has a positive and significant effect on organizational commitment; (3) Organizational Commitment has a positive and significant effect on Employee Loyalty; and (4) organizational commitment capable of mediating is able to mediate the effect of financial compensation on employee loyalty is significant, because the t statistic is greater than t table.Â